What Does Data Tell Us about Cross-border Online Learning? - Merola, Rachael (International Higher Education, 2017)
Cross-border online learning offers new ways to access education across borders without being physically present in the classroom. What does data indicate about the size and scale of the market, particularly in countries that are host to, and source of, many international students?